Effect of energy deprivation on metabolite release by anaerobic marine naphthalene‐degrading sulfate‐reducing bacteria. (3rd September 2020) - Chen, Gao; Widdel, Friedrich; Musat, Florin
Summary: The aromatic hydrocarbon naphthalene, which occurs in coal and oil, can be degraded by aerobic or anaerobic microorganisms. A wide‐spread electron acceptor for the latter is sulfate. Evidence for in situ naphthalene degradation stems in particular from the detection of 2‐naphthoate and [5, 6, 7, 8]‐tetrahydro‐2‐naphthoate in oil field samples. Because such intermediates are usually not detected in laboratory cultures with high sulfate concentrations, one may suppose that conditions in reservoirs, such as sulfate limitation, trigger metabolite release. Indeed, if naphthalene‐grown cells of marine sulfate‐reducing Deltaproteobacteria (strains NaphS2, NaphS3 and NaphS6) were transferred to sulfate‐free medium, they released 2‐naphthoate and [5, 6, 7, 8]‐tetrahydro‐2‐naphthoate while still consuming naphthalene. With 2‐naphthoate as initial substrate, cells produced [5, 6, 7, 8]‐tetrahydro‐2‐naphthoate and the hydrocarbon, naphthalene, indicating reversibility of the initial naphthalene‐metabolizing reaction. The reactions in the absence of sulfate were not coupled to observable growth. Excretion of naphthalene‐derived metabolites was also achieved in sulfate‐rich medium upon addition of the protonophore carbonyl cyanide4‐(trifluoromethoxy)phenylhydrazone or the ATPase inhibitor N, N′ ‐dicyclohexylcarbodiimide. In conclusion, obstruction of electron flow and energy gain by sulfate limitation offers an explanation for the occurrence of naphthalene‐derived metabolites in oil reservoirs, and provides a simple experimental tool for gaining insights into the anaerobic naphthalene oxidation pathway from an energetic perspective.